Phase I and pharmacokinetic study of an oral platinum complex given daily for 5 days in patients with cancer - McKeage, M J; Raynaud, F; Ward, J; Berry, C; O'Dell, D; Kelland, L R; Murrer, B; Santabárabara, P; Harrap, K R; Judson, I R (Journal of clinical oncology, 1997)
We aimed to determine the maximum-tolerated dose (MTD) clinical toxicities, pharmacokinetics, and pharmacodynamics of oral JM216 given once daily for 5 days to cancer patients. Patients who fulfilled standard phase I trial criteria were enrolled. Oral JM216 was given at doses based on patient body-surface area, on an empty stomach, once daily for 5 consecutive days, as 10-, 50-, and 200-mg hard gelatin capsules and with oral antiemetics. The pharmacokinetics of platinum were studied on days 1 and 5 of the first treatment course using atomic absorption spectrophotometry (AAS). Thirty-two patients received 94 courses of oral JM216 at doses that ranged from 30 to 140 mg/m2 body-surface area for 5 consecutive days. The MTD was 140 mg/m2/d. The dose-limiting toxicities were thrombocytopenia and neutropenia. Hematotoxicity was reversible (nadir, 17 to 21 days; recovery, 28 days), noncumulative, and dependent on the dose and history of previous therapy. There were two instances of neutropenic sepsis. Two-thirds of patients experienced mild nausea, vomiting, or diarrhea. There was no ototoxicity, neurotoxicity, nephrotoxicity, or objective tumor responses. There was a significant correlation between JM216 dose and the day 1 and 5 plasma ultrafiltrate area under the concentration-time curve (AUC; r = .78), which indicates linear pharmacokinetics. There was considerable intersubject pharmacokinetic and pharmacodynamic variability, but a significant sigmoidal relationship between the plasma ultrafiltrate AUC and severity of thrombocytopenia (R2 = .83). We recommend JM216 doses of 100 and 120 mg/m2/d x 5 for previously treated and untreated patients, respectively, for phase II trials.